Sustainability of Audit Excellence: Exploring Audit Knowledge, Audit Evidence, and Auditor Ethics in Enhancing Audit Quality - Rina Yuliastuty Asmara (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
This research aims to determine whether audit knowledge, audit evidence, and auditor ethics affect audit quality in public accounting firms. The study’s population includes 720 auditors who are registered public accountants at 36 public accounting firms in West Jakarta, with a sample size of 88 respondents. The findings of this research reveal that audit knowledge, combined with experience, is essential for ensuring audit quality. The analytical methods used include analyzing respondent characteristics, descriptive statistics, and inferential statistics using Partial Least Square (PLS). Consistent and reliable audit evidence positively influences audit quality. A high standard of auditor ethics positively affects audit quality, emphasizing the importance of adhering to professional ethical principles to ensure unbiased and accurate audit results within established standards. The study highlights that maintaining high levels of knowledge, experience, reliability of evidence, and ethical standards is integral to achieving quality audits. Moreover, the research underscores the concept of economic sustainability by demonstrating that sustained audit excellence contributes to the broader economic and social stability and trust in financial reporting systems. Achieving audit quality is characterized by adherence to established standards, and the absence of deviations supports the long-term economic, social, and environmental sustainability of public accounting practices.